Expanding the CURE: the impact of course-based undergraduate research experiences across natural and social sciences - Broussard, Christine; Gough Courtney, Margaret; Dunn, Sarah L.; Godde, K.; Preisler, Vanessa (Frontiers in Education, 2025)
IntroductionCourse-based Undergraduate Research Experiences (CUREs) are high-impact learning practices that replace the traditional apprenticeship model and can increase learning gains in diverse groups. We examined CUREs across disciplines (including the social and natural sciences) to evaluate performance at a Hispanic-Serving Institution.MethodsWe administered five instruments, including the CURE Survey of Course Elements, CURE Survey of Opinions, Experimental Design Ability Tool/Expanded Experimental Design Ability Tool, Career Adapt-Abilities Scale, and a demographic questionnaire. Wilcoxon Rank tests, Kolmogorov-Smirnov tests, and unpaired t-tests evaluated the efficacy of CUREs across students and within (and between) discipline type (social or natural science).ResultsSignificant positive learning gains were experienced for select instrument items, but not for career-ready skills. Natural science students displayed significant positive changes for three scientific practice skills, whereas social sciences students had greater positive changes for a different set of three scientific practice skills.DiscussionOverall, CUREs positively impacted student skills and self-perceptions.